The Power of Deed of Sale and Purchase of Land Under Hand - Raihandy Kevin Alexander Zulkarnain (Proceedings Series on Social Sciences & Humanities, 2023)
The practice of under-the-table land transactions, also known as "jual beli tanah dibawah tangan" in Indonesian, refers to the buying and selling of land without the involvement or oversight of official channels, such as government agencies or legal professionals. This phenomenon has gained significant attention due to its implications on land ownership, property rights, and the overall stability of the real estate market. This abstract aims to explore the various aspects of under-the-table land transactions, including the motivations behind such transactions, the methods used to conduct them, and the potential consequences for both buyers and sellers. It will examine the factors that contribute to the prevalence of this practice, such as legal complexities, bureaucratic inefficiencies, and cultural attitudes toward land ownership. The study will utilize a combination of qualitative and quantitative research methods, including interviews with real estate professionals, legal experts, and individuals involved in under-the-table land transactions. It will also analyze existing literature, case studies, and relevant legal frameworks to provide a comprehensive understanding of the issue. The findings of this research will contribute to a deeper understanding of the under-the-table land transactions phenomenon and its impact on land markets, governance, and socio-economic development. The study will shed light on potential policy interventions and regulatory measures that can be implemented to mitigate the negative consequences associated with these informal land transactions.